(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article proposes a reflection on three works by Joseph Beuys and a recent performance by Coletiva Animalia, focusing on the presence of non-human beings on stage. To this end, it brought together thinkers from animal studies and the performing arts, emphasizing the need to transform what we understand as multispecies scenes into cosmopolitically engaged scenes, as a new way of coexisting with other species in the face of the anthropocentric crisis.